Skarifikasi Benih Makadamia (Macadamia Integrifolia Maiden & Betche) Menggunakan Suhu Perendaman dan Pengeringan Secara Bergilir - Sunjaya Putra; Sumadi Sumadi; Anne Nuraini (Pusat Penelitian dan Pengembangan Perkebunan, 2019)
Macadamia can be propagated using seeds. However, the seed is difficult to germinate due to shell hardness. This study aimed to determine the proper combination of seed scarification needed to break the seed coat using rotational soaking and drying at varied temperatures. The experiment was conducted at Manoko Experimental Station and BPTP of West Java from December 2018 to April 2019, used a Randomized Complete Block Design in 15 treatments and 3 replications. The treatments were: (1) water soak (WS) 24oC+drying 35oC; (2) WS 35oC (first day)+WS 24oC+drying 35oC; (3) WS 50oC ( first day)+WS 24oC+drying 35oC; (4) WS 35oC everyday+drying 35oC; (5) WS 50oC everyday+drying 35oC; (6) WS 24oC+drying 40oC; (7) WS 35oC (first day)+WS 24oC+drying 40oC; (8) WS 50oC (first day)+WS 24oC+drying 40oC; (9) WS 35oC everyday+drying 40oC; (10) WS 50oC every day+drying 40oC; (11) WS 24oC+drying 45oC; (12) WS 35oC (first day)+WS 24oC+drying 45oC; (13) WS 50oC (first day)+WS 24oC+drying 45oC; (14) WS 35oC everyday+drying 45oC; and (15) WS 50oC everyday+drying 45oC. Variable observed were moisture content of seeds, rate and percentage of seeds cracking, and length of seeds radicle. The results showed that alternating temperature during soaking and drying affected seed scarification. The fastest seed breaking rate is 3.27 days in soaking at 50oC everyday for 18 hours, with 45oC drying temperature for 6 hours, the percentage of seed breaking reached 87.67%.